Single nucleotide polymorphism of BDNF Val66Met (rs6265) and its association to neuropsychiatric disorders - Asraa Faris; Cheah, Pike See; Ling, King-Hwa (Neurotak Publishing, 2020)
Brain-derived neurotrophic factor (BDNF) is the most abundant neurotrophin in the central nervous system and was shown to be involved in neuronal growth, differentiation and synaptic plasticity. A single nucleotide polymorphism at the pro-region of the BDNF gene (rs6265) has been reported to alter the amino acid from valine to methionine at codon 66 and was associated with neuropsychiatric disorders in several studies. To date, the results on the association of BDNF rs6265 to the aetiology of the neuropsychiatric illnesses have been inconsistent with some studies reporting a positive association and others reporting no association. Concerning the past inconsistent reports, this mini-review aims at determining the association of BDNF rs6265 and neuropsychiatric disorders among the different studies. Firstly, we discuss the findings on studies reporting the association of BDNF rs6265 with depression whereby a positive association between the BDNF variant and depression was obtained in several studies on the Caucasian, German, Chinese, and Malaysian population but not in studies on the Korean and other populations. Likewise, some studies found the occurrence of the SNP to be associated with a reduction in the BDNF level in depressed cases, but others found no effect at all. We then reported findings on the association of BDNF rs6265 with anxiety disorder, post-traumatic stress disorder, obsessive-compulsive disorder, panic disorder, bipolar disorder, and schizophrenia. Val allele has been found associated with these disorders, whereas some studies reported the involvement of the Met allele, and some reported no association at all. Similarly, the association of the BDNF variant with the BDNF level remains controversial. It is, therefore, essential to conduct more studies with larger sample sizes and look at the haplotype level to determine the association.